Hegemony in the Madurese Short Movie (Critical Discourse Analysis on Political Language in Indonesia) - Dzarna; Oktarini, Widya (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Madurese Short Movies are used not only as entertainments but also as a medium for instilling ideology and hegemony. The aim of this research is to reveal the practice of power or hegemony in Madurese short films between the government and society. Revealing the practice of power cannot be separated from the role of language used by the government towards society. The language used in politics contains power, so there needs to be a critical attitude that the public needs to know.The data obtained while watching YouTube is recorded for analysis. The hegemony analysis in this study uses Fairclough critical discourse analysis (CDA) dimension model in the form of description, interpretation, and explanation. The results of this research show that hegemony is found in Madurese short films with political themes through linguistic features (1) lexical processes, (2) metaphors, (3) declarative sentence mode, (4) relational modality, (5) personal pronouns. Hegemony through lexical processes shows childish elements carried out by characters that aim to win a goal. The lexical process shows the existence of hegemony between the authorities and society. The authorities use lexical processes that lead to childish attitudes by using the words gulatanah and jhâ' malek. In the metaphor aspect, there is hegemony, that is, the authorities use other terms to win the village elections. The use of metaphor leads to the expression, namely jhâ' kelopanmebelih copa, which means don't forget who helped in the village election process. In the declarative sentence mode, hegemony is telling the listener that this leader is not a kind of legacy so that anyone can become a leader. Meanwhile, the relational modality of hegemony tends to inform and invite people to choose the potential leader. In personal pronouns, hegemons tend to use the word "engko'" as evidence that this "engko'" has the power and strength to defeat the opponent. The conclusion of this research is that Madurese short films are used as a medium to maintain power, persuade, control and as a form of instilling ideology.